1973
DOI: 10.1063/1.1680629
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of CO(ν = 1) vibrational energy transfer rates using a frequency-doubled CO2 laser

Abstract: Laser-induced fluorescence studies of CO collisional relaxation have been carried out using the output of a frequency-doubled, pulsed CO2 laser as a direct source of CO(ν = 1) excitation. Energy transfer cross sections at 298 °K are reported for CO in collisions with He, Ar, H2, D2, N2, O2, Cl2, NO, CH4, CF4, and SF6. The D2–D2 self-relaxation rate was also obtained from the analysis of CO–D2 mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

1975
1975
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…The slower rise time observed in the transient absorption signals is due to the fact that products are produced in excited vibrational and rotational states and that vibrational relaxation to the probed ground state is significantly slower than the reaction rate. Previous experiments in our laboratory as well as measurements of vibrational relaxation rates have demonstrated that SF 6 is an effective buffer gas for the relaxation of CO 2 and N 2 O vibrational excitation. For CO, CF 4 is a more efficient relaxer of vibrational excitation and was therefore used as the buffer gas whenever CO was probed.…”
Section: Resultsmentioning
confidence: 92%
“…The slower rise time observed in the transient absorption signals is due to the fact that products are produced in excited vibrational and rotational states and that vibrational relaxation to the probed ground state is significantly slower than the reaction rate. Previous experiments in our laboratory as well as measurements of vibrational relaxation rates have demonstrated that SF 6 is an effective buffer gas for the relaxation of CO 2 and N 2 O vibrational excitation. For CO, CF 4 is a more efficient relaxer of vibrational excitation and was therefore used as the buffer gas whenever CO was probed.…”
Section: Resultsmentioning
confidence: 92%
“…Collisional energy transfer in carbon monoxide plays a significant role in atmospheric chemistry, 1, 2 astrophysics, [3][4][5] and condensed matter physics at ultra-cold temperatures. 6,7 It has been studied in the past both theoretically [8][9][10][11][12][13][14][15][16][17][18][19] and experimentally 3,18 in a broad range of temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 It has been studied in the past both theoretically [8][9][10][11][12][13][14][15][16][17][18][19] and experimentally 3,18 in a broad range of temperatures. For example, rotational-vibrational transitions of CO is a valuable diagnostic probe of diverse astrophysical environments, such as interstellar and circumstellar media, [20][21][22][23][24] where the temperatures of interest are very high, up to T ∼ 2500 K. Rovibrational transitions in the intermediate temperature range, 300 K < T < 1000 K, are important to the post-combustion kinetics of CO. [23][24][25] Finally, these processes play critical role in developing the methods for cooling (and trapping) molecules to (at) sub-Kelvin temperatures, because efficiency of experimental techniques depends on the ratio between elastic and inelastic scattering cross sections.…”
Section: Introductionmentioning
confidence: 99%
“…Using flash photoexcitation technique, Donovan and Husian obtained the quenching rate of 1.0 × 10 -14 cm 3 molecule -1 s -1 . To characterize temperature dependence, Miller and Millikan studied the excited CO molecules by infrared radiation and obtained a quenching rate of 7.8 × 10 -17 cm 3 molecule -1 s -1 at 300 K. In 1973, Green and Hancock measured k 1 - 0 to be 1.5 × 10 -16 cm 3 molecule -1 s -1 by laser-induced fluorescence. As indicated above, there is a large discrepancy of 2 orders of magnitude between the measured rate constants.…”
Section: Introductionmentioning
confidence: 99%